The concept of «Time» in signature worldview of Timur Zulfikarov (Eurasian Journal of Philology Science and Education, 2018)
«Time». Universal, national-cultural and individual layers are identified. It holds in-detail description of the «passive layer» of the concept of «Time». As the material of description the works of the famous contemporary poet and writer Timur Zulfikarov were considered. The researcher highlights language means that represent the concept of «Time»: lexical units in the literal sense – words with temporal color, metaphorical designations, comparisons, epithets, figurative associations, symbolic assimilation. The focusing on the context of language units representing the concept of «Time» gives an opportunity to reveal the periphery of the concept, to describe the meaning shades that are not fixed in any lexicographical sources, and finally to discover the peculiarities of studied concept in linguocultural aspect.